1986
DOI: 10.1073/pnas.83.23.8824
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a vasopressin isoreceptor in porcine seminal vesicles.

Abstract: Neurohypophysial hormones stimulate the motility of tunica albuginea, epididymis, and vas deferens acting through oxytocin (OT) and V1 vasopressin receptors. To test the hypothesis that these hormones are involved also in the regulation of seminal vesicle physiology, we studied binding of properties are distinct from the previously described V1 and V2 vasopressin receptors and indicate the presence of a new class of AVP receptors. Although this vasopressin isoreceptor shares some pharmacological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
2
7
1
Order By: Relevance
“…These results are in excellent agreement with our previous findings (Maggi et al, 1986). Similar binding specificity was obtained in medullopapillary membranes (Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…These results are in excellent agreement with our previous findings (Maggi et al, 1986). Similar binding specificity was obtained in medullopapillary membranes (Fig.…”
Section: Resultssupporting
confidence: 83%
“…In contrast, the renal cortex developed only non-specific binding (data not shown). The concentrations of AVP sites in seminal vesicles reported in the present study are 10-fold lower than those previously observed by us (Maggi et al, 1986 Dorsa et al, 1983). In the seminal vesicles AVP receptors were found in the epithelial cells facing the lumen of the glands.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…The homogenate was appropriately diluted, and 100 l containing 0.70 mg protein for androgen binding or 0.35 mg for estrogen binding were incubated overnight at 4 C in a final volume of 250 l in TEDGMo with increasing concentrations of [2,4,6,7,16, H]-estradiol (specific activity, 150 Ci/mmol), in the absence (0.015, 0.03, 0.06, 0.12 nmol/liter) or presence (0.12 nmol/liter) of increasing concentrations of nonradioactive 17␤-estradiol (10 Ϫ11 to 10 Ϫ5 mol/liter) for estrogen binding or with increasing concentrations of [ 3 H]R1881 (specific activity, 68 Ci/mmol) in the absence (0.125, 0.25, 0.5, 1 nmol/liter) or presence (1 nm) of increasing concentrations of nonradioactive R1881 (10 Ϫ10 to 10 Ϫ6 mol/liter) for androgen binding. Dilution of tracer was performed to optimally characterize the high-affinity portion of the displacement curves (26). To prevent R1881 binding to progesterone receptor (PR), 1 mol/liter triamcinolone acetonide was added to each tube.…”
Section: Binding Assaysmentioning
confidence: 99%